Baseline and Dynamic Expression of Activating NK Cell Receptors in the Control of Chronic Viral Infections: The Paradigm of HIV-1 and HCV - Marras, Francesco; Bozzano, Federica; Ascierto, Maria Libera; De Maria, Andrea (Frontiers in Immunology, 2014)
Natural Killer cell function is regulated by a balance between activating and inhibitory receptors expressed on their surface. .A relevant effort has focused so far on the study of KIR carriage/expression setting the basis for NK cell education and self-tolerance. Focus on the evolution and regulation of activating NK receptors has lagged behind so far. Our understanding of activating receptor expression and regulation has recently been improved by evidences derived from in vitro and in vivo studies.. Virus infection – either acute or chronic – has been shown to determine preferential expansion of NK cells with specific phenotypes and activating receptors and with recall-like functional activity.. Studies on patients with viral infection (HIV, HCV) and specific diverging clinical courses confirm that interindividual differences may exist in baseline expression of Natural Cytotoxicity receptors (NKp46, NKp30).. In addition, the findings that patients with divergent clinical courses have different kinetics of activating receptor density expression upon NK cell activation in vitro provides an additional “dynamic” dimension to the informations on basal receptor density expression., Different expression and inducibility of activating receptors on NK cells contribute to the high diversity of NK cell populations and may help our understanding of inherent interindividual differences in innate responses, underlying divergent disease courses